Relationship between physical strength measurements and anthropometric variables: multivariate analysis: 10.55131/jphd/2022/200111 - Malakar, Biswanath; Kumar Roy, Subrata; Pal, Baidyanath (Journal of Public Health and Development, 2022)
Muscular/ physical strength are fundamental in order to satisfy basic needs for survival and productivity, especially among labourer populations in developing countries. Anthropometric variables found to be one of the key determinants of strength; however, the overall relationship between physical body dimension and strength were yet to be explored. Aim of the study was to explore the relationship between strength and anthropometric variables. Crosssectional data on strength (handgrip and back strength) and anthropometric measurements were taken from 536 healthy adult Santal labourers (Male=251, Female=285) of Birbhum district, West Bengal, India. Statistical analysis including Pearson’s correlation and canonical correlation analysis (CCA) were used. Strength measurements negatively correlated with age and positively correlated with most of anthropometric measurements. CCA between strength and anthropometry were 0.765 (p<0.001, explained 85.53% total variance) and 0.611 (p<0.001, explained 71.41% total variance) for males and females respectively. Cross-loading value of CCA indicates fat-free-mass, forearm circumference and weight for male and fat-free mass, chest circumference and wrist breadth for female were most important predictors of strength. The CCA model indicate that fat-free mass, forearm circumference, weight, chest circumference and wrist breadth were the most important anthropometric variables related to overall strength measurements of Santal labourer population. However, further researches require for generalizing this model.